Extreme exposure advanced techniques for creative digital photography. - Nightingale, David Jonathan (East Sussex, UK Ilex, 2010)
With inspirational photography throughout, Extreme Exposure is the antithesis to this, setting out to liberate the enthusiast photographer. Covering the further ends of the exposure scale, this book explores the way in which cameras work both their limitations and potential before detailing how exposure can be used in a creative (and technical) fashion.
Technical considerations --Ultra-long shutter speeds --Ultra-short shutter speeds --Ultra-wide apertures --Ultra-small apertures.
Keywords: Photography -- Digital techniques